Perancangan Sistem Informasi Akuntansi Simpan Dan Pinjam Pada Koperasi Simpan Pinjam Jaya Kencana (KSPJK) - Nenden Yulia Siti Nurjanah; Iyeh Supriatna (Indonesian Accounting Literacy Journal, 2021)
Koperasi Simpan Pinjam Jaya Kencana (KSPJK) is a savings and loan cooperative that was established with the aim of improving the welfare of the residents of Bojong Seureuh and its surroundings. Activities in this cooperative are the same as savings and loan cooperatives in general, namely receiving savings from members to be used as capital to provide loans to other members who need it. The recording of savings and loan transactions at this cooperative is still manual and very simple, so that recording activities are hampered by consuming a lot of time. To solve existing problems, the authors are interested in designing a savings and loan accounting information system that suits your needs and can be applied to these cooperatives. The writer put forward the system design in this qualitative descriptive study. The accounting information system for savings and loans designed is expected to be implemented and help overcome any existing problems and improve employee performance.